Study of seasonality, impact of promotions and demand forecasting methods: based on the example of a company - Beja, Catarina maria pedro (2021)
Demand forecasting might be a challenging activity for any company. Actually, it is extremely difficult to predict the future trends, due to constant changes and increasing of complexity. An effective sales forecasting can become a core competence and help to surpass the competition. The present document was developed to assess the current ABC company’s demand forecasting method and to understand which factors can influence the sales of the company. Therefore, an analysis of seasonality, impact of promotions and forecasting methods was conducted. Thus, in this report both a forecasting method for the subcategory Ice Cream and an adjustment of promotions were suggested, allowing then for more accurate forecasting results.